2020
DOI: 10.1038/s41467-020-18301-2
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic susceptibility signatures identify potential antimicrobial targets in the Acinetobacter baumannii cell envelope

Abstract: A unique, protective cell envelope contributes to the broad drug resistance of the nosocomial pathogen Acinetobacter baumannii. Here we use transposon insertion sequencing to identify A. baumannii mutants displaying altered susceptibility to a panel of diverse antibiotics. By examining mutants with antibiotic susceptibility profiles that parallel mutations in characterized genes, we infer the function of multiple uncharacterized envelope proteins, some of which have roles in cell division or cell elongation. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
163
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(179 citation statements)
references
References 87 publications
(155 reference statements)
15
163
1
Order By: Relevance
“…advA (antibiotic susceptibility and division protein of Acinetobacter ) is another essential gene for A. baumannii growth. It has been shown that reduced AdvA levels modulated antibiotic susceptibility and generate a selective pattern of hypersensitivity to fluoroquinolones and β-lactams [ 38 ]. Avibactam could be a hypothetical mediator for sulbactam hypersensitivity through advA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…advA (antibiotic susceptibility and division protein of Acinetobacter ) is another essential gene for A. baumannii growth. It has been shown that reduced AdvA levels modulated antibiotic susceptibility and generate a selective pattern of hypersensitivity to fluoroquinolones and β-lactams [ 38 ]. Avibactam could be a hypothetical mediator for sulbactam hypersensitivity through advA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Tn-seq can be applied for the identification of genes required for resistance to bactericides ( Lai et al, 2017 ; Vitale et al, 2020 ) and potential antimicrobial target genes. For instance, the potential targets of multiple antibiotics were identified in the Acinetobacter baumannii via Tn-seq ( Geisinger et al, 2020 ). R. solanacearum is probably the most destructive plant pathogenic bacterium worldwide ( Mansfield et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with major health concerns in different regions of the world. These infections are responsible for about 1.5 million cases yearly (3,4).…”
Section: Introductionmentioning
confidence: 99%